Systemic Surcharges and Measures of Systemic Importance - Sigbjørn Atle Berg (Norges Bank, 2010)
There is an emerging consensus that systemically important banks should face stricter regulations and systemic surcharges. To make this latter principle operational we need to quantify the systemic importance of individual banks. This paper reviews the proposed measures of systemic importance from the regulatory and research communities and discusses their merits relative to how we would ideally wish to calibrate surcharges on systemically important banks.
hdl:11250/2507742
Keywords: 330